2021
DOI: 10.1063/5.0065222
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on all-optical Kerr switching for quantum optical applications

Abstract: We offer a perspective on recent advances in picosecond-timescale all-optical switching with applications in quantum optics. The switch is based on polarization rotation in standard single-mode fiber via the optical Kerr effect. By using ultrafast laser pulses and short (∼10 cm) fibers, this technique can achieve a switching duration of ≲1 ps, at the repetition rate of 80 MHz or above. This high repetition rate is well-suited to quantum optics where experiments operate in the photon-counting regime. The switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The Brewster angle-based graphene all-optical switch proposed is this study is an all-optical Kerr switch. 30 Optical Kerr switches can instantaneously generate a phase shift in the signal light field by controlling light pulses. In these switches, a switching operation is triggered when the phase shift of the signal light changes from 0 to π.…”
Section: Brewster Anglementioning
confidence: 99%
“…The Brewster angle-based graphene all-optical switch proposed is this study is an all-optical Kerr switch. 30 Optical Kerr switches can instantaneously generate a phase shift in the signal light field by controlling light pulses. In these switches, a switching operation is triggered when the phase shift of the signal light changes from 0 to π.…”
Section: Brewster Anglementioning
confidence: 99%
“…The polarization extinction required for the control pulse is approximately 100 dB for this fiber system. However, ultrafast nonlinear polarization rotation experiments, switching the polarization state of a photon using a control-pulse, show that the 100 dB isolation is possible in standard single-mode fiber with the use of two cross-polarizers [42].…”
Section: Asymmetric Dispersion Across Signal Pulse and Significant Pr...mentioning
confidence: 99%
“…Ultra-fast optical Kerr gates are widely used in ultra-fast spectrum measurements, 1 , 2 time-gate gating ballistic light imaging, 3 , 4 and third-order nonlinear measurements 5 . Moreover, they have immense potential in the field of quantum information 6 . In recent years, the performance improvement and optimization of ultrafast optical Kerr gates have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…5 Moreover, they have immense potential in the field of quantum information. 6 In recent years, the performance improvement and optimization of ultrafast optical Kerr gates have been studied. England et al 7 demonstrated an optical Kerr gate with an efficiency of up to 97% in single-mode fibers with a length of 10 cm.…”
Section: Introductionmentioning
confidence: 99%